Knowledge of physicians on chronic kidney disease and their attitudes towards referral, in two cities of Cameroon: a cross-sectional study. (December 2016) - Choukem, Simeon-Pierre; Nchifor, Pennghan; Halle, Marie-Patrice; Nebongo, Daniel; Mboue-Djieka, Yannick; Kaze, François; Monekosso, Gotlieb
Abstract Background Chronic kidney disease (CKD) is frequently unrecognized by non-nephrology physicians. There is an ongoing governmental program to create hemodialysis centers in the ten regions of Cameroon, where a previous study reported high levels of late referral to nephrologists. We aimed to assess the knowledge of physicians on CKD and their attitudes regarding referral. Methods A questionnaire based on the Kidney Disease Outcome Quality Initiative Guidelines of 2002 was self-administered to general practitioners and non-nephrology specialists working in two Cameroon cities that have hemodialysis centers (Douala and Bamenda). Results Of the 174 general practitioners and non-nephrology specialists approached, 114 (65.5 %) returned answered questionnaires. Only 58.8 % of doctors identified the correct definition of CKD. Most physicians were aware of the major risk factors of CKD (hypertension, 97.4 % and diabetes mellitus, 95.6 %). Most physicians were also aware of complications such as anemia (93.0 %), hypertension (90.4 %), uremia (85.1 %) and hyperkalemia (85.1 %). Only 44 % knew that CKD had five stages, with general practitioners 3.4 times more likely to know than specialists (p = 0.004). Even though 61.4 % of the physicians knew that the estimated glomerular filtration rate was the appropriate clinical means to diagnose CKD, 12.7 % would use serum creatinine alone for diagnosis. Also, up to 21.9 % of physicians would refer at late stage. Conclusion General practitioners and non-nephrology specialists lack general knowledge on CKD, especially on the definition and staging; they also have inadequate attitudes with regards to diagnosis and referral to the nephrologists. Educational efforts are warranted to improve on physicians' knowledge and skills on CKD in Cameroon.